An advanced bionic knee joint mechanism with neural network controller - Xu, Changxian; Sun, Zhongbo; Wang, Chen; Wu, Xiujun; Li, Binglin; Zhao, Liming (Frontiers in Neurorobotics, 2023)
In this paper, a tensegrity based knee mechanism is investigated for the purpose of developing a high efficiency rehabilitation knee exoskeleton. Besides, the kinematics and dynamics models of the knee mechanism are explored for further controller design. In addition, for the purpose of studying the bionic knee joint performances, based on the limit function of knee patella, the limit functionality of the bionic knee joint is developed for enhancing the bionic property. Furthermore, for eliminating the noise item and other disturbances that certainly generated in the rehabilitation process, a noise-tolerant zeroing neural network (NTZNN) algorithm is utilized to establish the controller. Which means the controller has the performance of anti-noise, hence, it is quite unique with other bionic knee mechanism controller. Eventually, the anti-noise performance and calculating precision of the NTZNN controller are verified through several simulations and contrast results.